دور يوم طلاب المعاهد الإسلامية الوطني في تعزيز الحافز اللغوي وتنمية مهارة الكلام لدى طلاب معهد التبيان بديلي سردانج - Mhd Firdaus Lubis; Mohammed Abdulaziz Mohammed Ahmedeltigani (Program Studi Pendidikan Bahasa Arab (PBA), Universitas Islam Negeri Datokarama Palu, 2026)
This study is grounded in the importance of developing speaking skills as the core of communicative competence in Arabic language learning within Islamic boarding schools, which is still largely dominated by theoretical approaches and limited classroom practices. Previous studies have tended to examine language environment, instructional strategies, or motivation separately, without addressing their integration within inter-institutional interactive contexts. Therefore, this study aims to analyze the role of the National Islamic Boarding School Students’ Day in enhancing language motivation and developing students’ speaking skills at Ma’had At-Tibyan. This research employs a qualitative approach with a case study design, using observation, in-depth interviews, and documentation, analyzed through the Miles and Huberman model. The findings indicate that this program effectively integrates intrinsic and extrinsic motivation into actual communicative practices through language competitions, inter-student interactions, and collaborative activities, leading to improvements in fluency, confidence, and vocabulary mastery. Furthermore, cross-institutional interaction strengthens students’ self-evaluation and linguistic adaptability, despite challenges such as language anxiety and varying proficiency levels. In conclusion, this program functions as an interactive pedagogical space that effectively transforms language motivation into sustainable speaking practice.